2018
DOI: 10.1159/000495386
|View full text |Cite
|
Sign up to set email alerts
|

Early Start Peritoneal Dialysis: Technique Survival in Long-Term Follow-Up

Abstract: Background/Aims: Peritoneal dialysis (PD) has gained interest over the last decade as a viable option for early start dialysis. It is still unknown if shorter break-in periods and less time for proper patient evaluation and training could influence technique survival in comparison to planned-start PD. Methods: A prospective and observational study that compared technique survival in a cohort of patients who started either early or planned PD. Early start PD was defined as break-in period from 3 to 14 days with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…Eleven of the included studies 2,18 27 compared the outcomes of urgent-start PD with those of planned PD, three 28 30 compared the outcomes of urgent-start PD with those of urgent-start HD, whereas one study 31 compared the outcomes of urgent-start PD with those of both planned PD and urgent-start HD concurrently. In the only RCT study, 27 participants were randomized to the urgent-start PD group or the planned PD group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven of the included studies 2,18 27 compared the outcomes of urgent-start PD with those of planned PD, three 28 30 compared the outcomes of urgent-start PD with those of urgent-start HD, whereas one study 31 compared the outcomes of urgent-start PD with those of both planned PD and urgent-start HD concurrently. In the only RCT study, 27 participants were randomized to the urgent-start PD group or the planned PD group.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported outcomes observed during the short-term follow-up, two studies 21,22 reported technique survival in a longer follow-up. Two studies 18,26 reported different follow-up periods between the two groups; thus, data pertaining to this subject were not extracted for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent review [13] also demonstrated that using the lowest possible dwell volume based on patient’s size and keeping the patient in strict supine position during treatment for initial 2 weeks were the most critical factors in minimizing the risk of catheter leaks and malfunction. Furthermore, recent studies [29, 30, 38] showed that immediate PD after catheter insertion is feasible, catheter implantation technology might have contributed to the mechanical complication. Stegmayr [18] reported that optimizing the success rate for PD catheter placement requires physicians to focus on insertion of the catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, the early technique survival rate varies from 75% (unplanned-start PD) versus 86.5% (conventional PD) at 3 months to 68 versus 80% at 1 year, which showed that unplanned-start PD might be detrimental to early technique survival of patients. However, a number of observational studies showed that PD initiated immediately after catheter insertion might have no major effect on technique survival [25, 30, 31]. Younger patient population, lower incidence of comorbidities, and better center management were the possible reasons to explain that.…”
Section: Discussionmentioning
confidence: 99%